Characteristics of Patients with Severe Heart Failure Exhibiting Exercise Oscillatory Ventilation. (July 2013) - Matsuki, Ryosuke; Kisaka, Tomohiko; Ozono, Ryoji; Kinoshita, Hiroki; Sada, Yoshiharu; Oda, Noboru; Hidaka, Takayuki; Tashiro, Naonori; Takahashi, Makoto; Sekikawa, Kiyokazu; Ito, Yoshihiro; Kimura, Hiroaki; et al.
<x xml:space="preserve">Abstract</x> This study aims to elucidate the characteristics of patients with severe nonischemic heart failure exhibiting exercise oscillatory ventilation (EOV) and the association of these characteristics with the subjective dyspnea. Forty-six patients with nonischemic heart failure who were classified into the New York Heart Association (NYHA) functional class III underwent cardiopulmonary exercise testing (CPX) and were divided into two groups according to the presence or absence of EOV. We evaluated the patients by using the Specific Activity Scale (SAS), biochemical examination, echocardiographic evaluation, results of CPX and symptoms during CPX (Borg scale), and reasons for exercise termination. EOV was observed in 20 of 46 patients. The following characteristics were observed in patients with EOV as compared with those without EOV with statistically significant differences: more patients complaining dyspnea as the reason for exercise termination, lower SAS score, higher N-terminal pro-brain natriuretic peptide level, larger left atrial dimension and volume, left ventricular end-diastolic volume, higher Borg scale score at rest and at the anerobic threshold, higher respiratory rate at rest and at peak exercise, and higher slope of the minute ventilation-to-CO2 output ratio, and lower end-tidal CO2 pressure at peak exercise. Among the subjects with NYHA III nonischemic heart failure, more patients with EOV had a stronger feeling of dyspnea during exercise as compared with those without EOV, and the subjective dyspnea was an exercise-limiting factor in many cases.